Spatial Distribution of Wall Shear Stress in Common Carotid Artery by Color Doppler Flow Imaging - Wang, Chao (Springer-Verlag, 2012)
The purpose of this study is to provide a novel approach for measuring the spatial distribution of wall shear stress (WSS) in common carotid artery in vivo. WSS distributions were determined by digital image processing from color Doppler flow imaging (CDFI) in 50 healthy volunteers. In order to evaluate the feasibility of the spatial distribution, the mean values of WSS distribution were compared to the results of conventional WSS calculating method (Hagen–Poiseuille formula). In our study, the mean value of WSS distribution from 50 healthy volunteers was (6.91 ± 1.20) dyne/cm(2), while it was (7.13 ± 1.24) dyne/cm(2) by Hagen–Poiseuille approach. The difference was not statistically significant (t = −0.864, p = 0.604). Hence, the feasibility of the spatial distribution of WSS was proved. Moreover, this novel approach could provide three-dimensional distribution of shear stress and fusion image of shear stress with ultrasonic image for each volunteer, which made WSS “visible”. In conclusion, the spatial distribution of WSS could be used for WSS calculation in vivo. Moreover, it could provide more detailed values of WSS distribution than those of Hagen–Poiseuille formula. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10278-012-9505-3) contains supplementary material, which is available to authorized users.